Business Intelligence Analysis and Design to Improve Revenue Performance at Holding Companies - Syaiful Rachman; Dina Anggraini (Budapest International Research and Critics University, 2022)
COVID-19 Virus Disease 2019 (COVID-19) is rapidly spreading around the world, so the world economy is hit by a major crisis. Government policies for restrictions on activities make the company experience a significant decrease in revenue, especially for companies in the field of property and hotels, so the need for information on the entire business process of the company becomes one of the important needs for the survival of the company. Business Intelligence (BI) is one of the solutions for companies' needs, especially in analyzing and providing access to data to help make better decisions. Companies need dashboards to process data into information, so that decision-making can be used to support business processes that are running in the midst of a pandemic. Therefore, a Business Intelligence dashboard is needed to analyze revenue data that can be used to improve the performance of each branch in the company. The stages of making a BI dashboard are literature study, justification, planning, business analysis, design, construction, and report. The results of this study are visualizations in the form of graphs of PT JSI Tbk's revenue, Company revenue, Branch revenue, and Branch revenue in 2021. Based on the results of the prototype of the BNV, PM, and HCR branches must be creative in improving performance or operational cost efficiency.